2022
DOI: 10.12998/wjcc.v10.i32.11671
|View full text |Cite
|
Sign up to set email alerts
|

Role of adherent invasive Escherichia coli in pathogenesis of inflammatory bowel disease

Abstract: Gut microbiota imbalances play an important role in inflammatory bowel disease (IBD), but no single pathogenic microorganism critical to IBD that is specific to the IBD terminal ileum mucosa or can invade intestinal epithelial cells has been found. Invasive Escherichia coli ( E. coli) adhesion to macrophages is considered to be closely related to the pathogenesis of inflammatory bowel disease. Further study of the specific biological characteristics of adherent inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 138 publications
1
8
0
Order By: Relevance
“…Enterobacteriaceae has been reported to increase progressively with aging [68]. Enterobacteriaceae can induce in ammation in the host by releasing endotoxins which can contribute to muscle wasting and metabolic dysfunction [69,70]. The association found between obesity and Enterobacteriaceae in previous studies [71] further indicated the impact of combined obesity in myasthenia gravis on the gut bacterial community, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
“…Enterobacteriaceae has been reported to increase progressively with aging [68]. Enterobacteriaceae can induce in ammation in the host by releasing endotoxins which can contribute to muscle wasting and metabolic dysfunction [69,70]. The association found between obesity and Enterobacteriaceae in previous studies [71] further indicated the impact of combined obesity in myasthenia gravis on the gut bacterial community, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 91%
“…To examine whether the migration ability of the AIEC LF82 strain was enhanced, the swimming motility of the bacterium was measured using Luria Bertani (LB) medium containing 0.3% agar [ 9 ]. The swimming diameters of the AIEC LF82 strain were significantly greater than those of the non-AIEC K12 strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial invasion is promoted by the binding of bacterial outer membrane proteins ( OmpA ) to the ER-stress response chaperone, Gp96, which is strongly expressed on the apical surface of ileal epithelial cells [ 7 , 8 ]. The specific adhesion and invasiveness of AIEC are believed to strongly contribute to the development and pathogenesis of CD, especially the postoperative recurrence [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…To examine whether the migration ability of the AIEC LF82 strain was enhanced, the swimming motility of the bacterium was measured using LB medium containing 0.3% agar (10). The swimming diameters of the AIEC LF82 strain were signi cantly greater than those of the non-AIEC K12 strains (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The speci c adhesion and invasiveness of AIEC is belived to strongly contribute to the development and pathogenesis of CD, especially the postoperative recurrence (10).…”
Section: Introductionmentioning
confidence: 99%